Acute Rejection of White Adipose Tissue Allograft - Vitaly Ablamunits; Alan J. Goldstein; Marina H. Tovbina; Harold P. Gaetz; Simon Klebanov (Cell Transplantation, 2007)
White adipose tissue (WAT) transplantation, although widely used in humans, has been done for cosmetic and reconstructive purposes only. Accumulating evidence indicates, however, that WAT is an important endocrine organ and, therefore, WAT transplantation may become valuable as a replacement therapy for a number of hereditary human diseases. Because the most readily available source for such transplantations would be allogeneic tissue, the mechanisms involved in the rejection of WAT allograft should be explored. We have established a model in which leptin-producing allogeneic WAT is transplanted into leptin-deficient ob/ob mice. Because ob/ob mice are obese, hyperphagic, and hypothermic, WAT allograft function is monitored as the reversal of this leptin-deficient phenotype. Here we report that allografted WAT is primarily nonfunctional. However, when WAT is transplanted into immunodeficient (Rag1–/–) ob/ob mice, or into ob/ob mice depleted of T cells by anti-CD3 antibody, a long-term graft survival is achieved as indicated by the reversal of hyperphagia, weight loss, and normalization of body temperature. The symptoms of leptin deficiency rapidly recur when normal spleen cells of the recipient type are injected, or when the antibody treatment is terminated. In contrast, selective depletion of either CD4+ or CD8+ cells alone does not prevent WAT allograft rejection. Similarly, WAT allografts that do not express MHC class I or class II molecules are rapidly rejected, suggesting that both CD4+ and CD8+ T cells may independently mediate WAT allograft rejection.